Exploring the interaction between growth mindset and self-efficacy in predicting English as a foreign language learning achievement - Cai, Yuyang (Studies in Second Language Learning and Teaching, 2026)
Growth mindset has been a hot topic in English as a second or foreign language (L2) research. Despite its popularity, a growth mindset is not always found to benefit L2 learning achievement. A major reason for this complexity has been ascribed to the interference of other variables. The current study focused on the interplay between self-efficacy and growth mindset in impacting L2 (English) learning achievement. Specifically, the study tested three forms of interaction: competition, mediation, and moderation. Participants included 367 second-year students from a Chinese university who were recruited through convenient sampling. The results of structural equation modeling after controlling for variances at the teacher level showed that: (1) self-efficacy played a dominant role in predicting English achievement (confirming competition); (2) self-efficacy did not mediate the relationship between growth mindset and English achievement (disconfirming mediation), and (3) growth mindset amplified the relationship between self-efficacy and English achievement (confirming moderation). Findings from the interaction analyses suggest that growth mindset serves as an amplifier strengthening the association between self-efficacy and English achievement. Therefore, instruction should not only focus on fostering self-efficacy but also on boosting a growth mindset to optimize learning efficiency.